Study of glomerular filtration rate in patients with metabolic syndrome - G., Prakash K.; S., Rashmi (International Journal of Advances in Medicine, 2020)
Background: Chronic kidney disease is a major risk factor for end stage renal disease, cardiovascular events and death. Various studies have shown an association between metabolic syndrome and CKD. Even mild renal insufficiency increases the risk for cardiovascular events. This study was conducted to detect CKD in its early stages which are characterized by mildly reduced GFR in patients with metabolic syndrome. Methods: This is a cross sectional study of 60 patients, 30 with metabolic syndrome diagnosed on the basis of IDF criteria and 30 controls. EGFR was calculated using the CKD-EPI formula and the results between the two groups was analysed using chi square test for statistical significance. Results: In this study conducted on 60 patients, age distribution was between 20 and 60 years. Male to female ratio was 1:1.06. 26.66% of the cases had normal GFR while among the controls, 46.66% had normal GFR. Out of the 30 cases, 53.33% had mildly reduced GFR while out of the controls, 23.33% had mildly reduced GFR. This association between metabolic syndrome and mildly reduced EGFR was found to be significant (p≤0.05). Conclusions: The results of this study showed that metabolic syndrome is associated with a mildly reduced GFR and hence early detection of these risk factors is essential for treatment and prevention of CKD.